The Impact of a Three-Step Interview on Students’ Speaking Ability - Arafah, Rifda; Danim, Sudarwan; Dharmayana, Wayan; Anshori, Sakut; Prihantoro, Prihantoro (ENGLISH FRANCA : Academic Journal of English Language and Education, 2021)
The goal of this study was to determine the impact of employing a Three-Step Interview on students' speaking abilities. This study's population consisted of all 80 students in their first year at MAN Talang Leak Kabupaten Lebong. The sample consisted of 56 individuals drawn from two courses. The students were separated into two groups: the experimental group got therapy utilizing the Three-Step-Interview method, while the control group was taught using traditional methods. The data will be collected using several methods in the exam. The pre-test will be given once before the therapy begins, and the post-test will be given once the study is completed. This research includes seven treatment meetings. It is based on MAN Talang Leak's academic timetable and semester program. The post-test would be given to the students after they had received seven treatments for each topic. The results from this study will be statistically analyzed using the t-test for the pre-and post-tests. The post-test will be used to collect data on the influence of using the Three-Step-Interview method on students' speaking performance. The disparity between the two classes was substantial. According to the data analysis, the outcome demonstrates that the Three-Step-Interview approach may increase students' speaking abilities. It is possible to conclude that the usage of the Three-Step-Interview had a beneficial influence on students' speaking skills. Based on the findings, teachers are advised to utilize the Three-Step-Interview approach when training senior high school pupils to talk.